Al-Masā’il allatī istadraka al-Qāḍī Ibn Rusyd -al-Ḥafīd- [t. 595 H] ‘alā Abī Ḥāmid al-Ghazālī [t. 505 H] baḥtsahā fī ‘ilm uṣūl al-fiqh min khilāl mukhtaṣarihī li al-Mustaṣfā: Jam‘an wa Dirāsah: المسائل التي استدرك القاضي ابن رشد -الحفيد- [ت 595هـ] على أبي حامد الغزالي [ت 505ه] بحثها في علم أصول الفقه من خلال مختصره للمستصفى )جمعاً ودراسة( - Abdel Hady, Ahmed Mohamed (Rayah Al-Islam, 2026)
The primary purpose of this research is to comprehensively elaborate on the distinctiveness of fundamental issues in the science of usul al-fiqh and to purify this discipline from external elements that cause confusion among students. To achieve this objective, the research employs a qualitative method through inductive and deductive approaches to analyze classic texts, specifically focusing on data collection from Ibn Rushd's Mukhtasar Al-Mustashfa. The results and discussion clearly demonstrate that Ibn Rushd Al-Hafid significantly contributed to the trajectory of istidrak and scientific correction. Specifically, he corrected Al-Ghazali's views on eleven different issues encompassing theology, jurisprudence, and grammar that were inappropriately incorporated into usul al-fiqh. The analysis concludes that Ibn Rushd's perspectives in these corrections are precise and accurate. The impact of this research lies in its specific focus on reaffirming the epistemological boundaries of usul al-fiqh, ensuring it remains pure and unmixed with other disciplines, which provides a fresh perspective in analyzing classical literature critically